EFFECT OF BUDGET PARTICIPATION ON MANAGERIAL PERFORMANCE MEDIATED BY JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Widiawati, Devi; RS, Tantri Yanuar (JOURNAL OF BUSINESS STUDIES, 2019)
Budget usage within University of Sultan Ageng Tirtayasa is considered as not proportionally used. It can be seen from the budget usage that has not been maximized.Overcoming the budget usage and also improving managerial performance is requiring the involvement of a manager in the preparation of the budget. As some theories and studies shows that managerial performance can be affected by the budget participation, this case in University of Sultan Ageng Tirtayasa can be assessed based on the theories, this also check the relationship when mediated by organizational commitment and job satisfaction. The aim of this study was to determine the effect of budget participation on managerial performance with the mediation of organizational commitment and job satisfaction. The study was conducted by collecting quantitative data, with questionnaires distributed to 45 respondents, as the total received 36 back in the form of data that can be processed.This data is then analyzed by Structural Equation Model with Partial Least Square (PLS-SEM). The results indicate that the hypothesis is accepted, the participation of high budget can affect organizational commitment, high participation can influence job satisfaction, job satisfaction and organizational commitment of high influence managerial performance. In addition, based on the results of path analysis showed that job satisfaction is higher influence because rather than organizational commitment.